ANALISIS HUKUM PIDANA MATERIL DAN FORMIL TERHADAP PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG DI INDONESIA - Adhelfy Prabas; Zulfikar Jayakusuma; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
In the concept of the rule of law, everything that is contrary to applicable rules must be held accountable, especially when it comes to money laundering. Some of the problems that are still deeply attached to money laundering include the meaning of the crime itself, then related to the perpetrators and the issue of accountability as well as sanctions given by law enforcement officials in combating money laundering. As for the purpose of writing this thesis, namely: First, to find out the extent of the enactment of material and formal criminal law against the eradication of money laundering in Indonesia, Second, to find out what are the efforts made to eradicate the crime of money laundering in IndonesiaThis type of research is normative juridical research, namely research conducted by examining secondary legal materials or research based on standard rules that have been recorded and discussing the principles of law and synchronizing the law. Data sources used in this study are primary data, secondary data and tertiary data.From the results of this study it can be concluded that in analyzing material and formal criminal law against eradicating money laundering, there are still some weaknesses so that it is not yet maximized in its implications. First, by emphasizing that there should be a re-harmonization or revision of the money laundering law which still has some shortcomings or gaps in its application. So with that case can produce a good legal product. Second, by strengthening regulations, increasing the reference standards of financial institutions,Keywords: Analysis – Eradiction - Money Laundering